Role of Diuretics and Ultrafiltration in Congestive Heart Failure - Jo Ann Lindenfeld; Robert Schrier; Fawaz Al Ammary; Dmitry Shchekochikhin (MDPI AG, 2013)
Volume overload in heart failure (HF) results from neurohumoral activation causing renal sodium and water retention secondary to arterial underfilling. Volume overload not only causes signs and symptoms of congestion, but can impact myocardial remodeling and HF progression. Thus, treating congestion is a cornerstone of HF management. Loop diuretics are the most commonly used drugs in this setting. However, up to 30% of the patients with decompensated HF present with loop-diuretic resistance. A universally accepted definition of loop diuretic resistance, however, is lacking. Several approaches to treat diuretic-resistant HF are available, including addition of distal acting thiazide diuretics, natriuretic doses of mineralocorticoid receptor antagonists (MRAs), or vasoactive drugs. Slow continuous veno-venous ultrafiltration is another option. Ultrafiltration, if it is started early in the course of HF decompensation, may result in prominent decongestion and a reduction in re-hospitalization. On the other hand, ultrafiltration in HF patients with worsening renal function and volume overload after aggressive treatment with loop diuretics, failed to show benefit compared to a stepwise pharmacological approach, including diuretics and vasoactive drugs. Early detection of congested HF patients for ultrafiltration treatment might improve decongestion and reduce readmission. However, the best patient characteristics and best timing of ultrafiltration requires further evaluation in randomized controlled studies.